LABOR MIGRATION FROM UKRAINE TO THE EU ON THE EXAMPLE OF POLAND: KEY TRENDS AND PROBLEMS ASPECTS IN THE CONTEXT OF EUROPEAN INTEGRATION - OSIPOVA, LARISA; KRAVCHYK, YURII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article summarizes the current state and main trends of external migration of the population from Ukraine to the Republic of Poland, in particular in the aspect of labor migration. The political and legal regime of border crossing between countries is described. The characteristics of key economic and social parameters that determine the migration environment in the Ukraine - Poland system are given. Indicators of border crossing by Ukrainians to Poland, residence of Ukrainian citizens on the territory of Poland, their place in the gender structure of the population of this country, naturalization are given. The results of the analysis of tendency characteristics of external labor migration from Ukraine to the Republic of Poland in terms of the number of submitted applications and received permits for temporary stay and employment of Ukrainians in Poland are reflected. The specifics, as well as problematic aspects of external labor migration from Ukraine to Poland in the context of socio-economic development of countries, as well as European integration of Ukraine.The shortcomings of increasing labor migration from Ukraine to Poland, such as the rapid increase in the number of Ukrainian citizens living in Poland, including in the structure of foreigners, have been identified; increasing the number and increasing the dynamics of applications submitted and permits obtained for temporary stay of Ukrainians in Poland, especially for reasons of work and study; growing intentions of Ukrainians and increasing the number of permits obtained for the right to perform long-term work in Poland; further strengthening the attitudes and attitudes of Ukrainians regarding the intensification of their plans and intentions regarding the implementation of various forms of migration to Poland; increase in the number of naturalization practices of Ukrainian citizens by Poland, which is evidence of the growing threat not only of high migration rates, but also changes in citizenship by domestic migrants.The practical significance of the research results lies in the formation of information and analytical support for the formation and implementation of state policy regulating migration processes in the migration system Ukraine - EU to accelerate Ukraine's European integration processes and realize the potential of socio-economic development.The scientific novelty of the study lies in the scientific approach to solving the problem of development and realization of migration potential in the Ukraine – EU system on the example of the recipient - the leader in attracting labor migrants from Ukraine – the Republic of Poland.
Keywords: Ukraine's integration into the EU; labor migration; migration processes; migration activity; the impact of migration on socio-economic development